2007
DOI: 10.1634/stemcells.2007-0454
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptors 3 and 4 Are Expressed by Human Bone Marrow-Derived Mesenchymal Stem Cells and Can Inhibit Their T-Cell Modulatory Activity by Impairing Notch Signaling

Abstract: STEM CELLS 2008;26:279 -289 Disclosure of potential conflicts of interest is found at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
409
6
19

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 446 publications
(457 citation statements)
references
References 69 publications
19
409
6
19
Order By: Relevance
“…54 Moreover, engagement of TLR-4 on MSC by lipopolysaccharide has been shown to result in the generation of pro-inflammatory MSC 55 and to suppress their immunosuppressive activity, 56 although this is still a matter of debate. 57 Whether HMGB1 induces a similar phenotype in MSC is currently being determined.…”
Section: Migration Of Msc Towards Recombinant Hgf Was Inhibitedmentioning
confidence: 99%
“…54 Moreover, engagement of TLR-4 on MSC by lipopolysaccharide has been shown to result in the generation of pro-inflammatory MSC 55 and to suppress their immunosuppressive activity, 56 although this is still a matter of debate. 57 Whether HMGB1 induces a similar phenotype in MSC is currently being determined.…”
Section: Migration Of Msc Towards Recombinant Hgf Was Inhibitedmentioning
confidence: 99%
“…Activation of human MSCs by TLR ligands induces IL-6, IL-8 and CXCL10 secretion and NF-kB nuclear translocation in vitro (Liotta et al, 2008). TLR 3 and 4 ligation via lipopolysaccharide (LPS) reduces the suppressive activity of MSCs on proliferating T cells (Tomchuck et al, 2008), while increasing their reprogramming capacity on macrophages by a prostaglandin (PG) E2-dependent mechanism (Nemeth et al, 2009).…”
Section: Modulation Of Immune Responsesmentioning
confidence: 99%
“…Recently, several reports showed that engagement of different Toll-like receptors (TLRs) in MSCs either enhanced or inhibited their immunosuppressive properties [11][12][13]. mostly immunosuppressive ones [12].…”
Section: Introductionmentioning
confidence: 99%